2022
DOI: 10.1093/jcr/ucac020
|View full text |Cite
|
Sign up to set email alerts
|

Get Your Science Out of Here: When Does Invoking Science in the Marketing of Consumer Products Backfire?

Abstract: In this research, we propose that although consumers view the scientific process as competent, they also perceive it as cold. Across ten experimental studies, we demonstrate that these lay beliefs impact consumers’ reactions to marketers touting the science behind their brands. Specifically, since hedonic attributes are associated with warmth, the coldness associated with science is conceptually disfluent with the anticipated warmth of hedonic products and attributes, reducing product valuation. In contrast, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…Prior research suggests that incidental factors such as font usage (Novemsky et al 2007), figure–ground contrast (Reber and Schwarz 1999), and semantic priming (Kelley and Lindsay 1993) can all alter ease of processing. Further, factors integral to the focal problem, such as linguistic ease (Alter and Oppenheimer 2009) or prototypicality of the target (Winkielman et al 2006), or congruity with one's lay beliefs (Philipp-Muller, Costello, and Reczek 2022), can alter perceived processing ease. In the context of reviews, we expect two integral factors to be particularly relevant to reducing processing ease and hence to attenuate or even eliminate the effect of content similarity on helpfulness: review text difficulty and photo quality.…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…Prior research suggests that incidental factors such as font usage (Novemsky et al 2007), figure–ground contrast (Reber and Schwarz 1999), and semantic priming (Kelley and Lindsay 1993) can all alter ease of processing. Further, factors integral to the focal problem, such as linguistic ease (Alter and Oppenheimer 2009) or prototypicality of the target (Winkielman et al 2006), or congruity with one's lay beliefs (Philipp-Muller, Costello, and Reczek 2022), can alter perceived processing ease. In the context of reviews, we expect two integral factors to be particularly relevant to reducing processing ease and hence to attenuate or even eliminate the effect of content similarity on helpfulness: review text difficulty and photo quality.…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…This result is similar to those of Philipp-Muller et al's study (2022) but differs in its mechanism. Philipp-Muller et al (2022) found that citing science in advertisements can lower people's attitudes toward hedonic products; they attributed it to the negative impact of the mismatch between the indifference accompanying science and the warmth accompanying hedonic products on processing fluency. Even if science is without using unfamiliar language to consumers, it can have a negative impact due to a decrease in matching fluency.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…Incomprehensible descriptions in ad copy lead to increased negative attitudes toward the product and decreased purchase intention (Baskin & Liu, 2021). Technical language, which is often associated with science, is connected to coldness and can reduce consumers' willingness to purchase hedonic products (Philipp‐Muller et al, 2022). This series of studies shows that the use of technical language in advertising can reduce consumers' purchase intentions.…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…Surprisingly little research has examined how categorizing someone or something as "artistic" versus "scientific" affects judgments, even though these labels are prominently used and frequently contrasted in everyday experience. For example, people describe skills and activities as "more art than science" (and vice versa; Mihm, 2022) and people as "artsy" or "science-y" (Feist, 1998;Pearson, 2016). Individuals hold bachelor of arts or bachelor of science degrees; governments allocate separate funding for arts and sciences; marketers frame products as more artistic or scientific (Philipp-Muller et al, 2023).…”
Section: Distinct Categories Of Social Judgmentmentioning
confidence: 99%
“…For example, people describe skills and activities as "more art than science" (and vice versa; Mihm, 2022) and people as "artsy" or "science-y" (Feist, 1998;Pearson, 2016). Individuals hold bachelor of arts or bachelor of science degrees; governments allocate separate funding for arts and sciences; marketers frame products as more artistic or scientific (Philipp-Muller et al, 2023). Yet the implications of these categorizations for social judgment remain understudied.According to prior literature, when people, activities, works, and so on are categorized as artistic, it suggests that they involve emotion, imagination, intuition, or all three (Bullot & Reber, 2013).…”
mentioning
confidence: 99%